Lessons learned from using shadowing as a qualitative research technique in Education. Issue 1 (2nd January 2016) - Ferguson, Kristen
Abstract: While shadowing is known in disciplines such as Organizational Studies, there is little reference to shadowing as a qualitative research technique in Education or other social science fields. This paper explores shadowing in the research literature and my experience collecting data using shadowing. Using my researcher journal and reflections, I present five lessons learned as a qualitative shadowing researcher in Education: shadowing is difficult, tiring and time consuming; shadowing is high stakes emotionally for the participants; participants have control during data collection, researchers have control with the results; shadowing researchers must manage relationships with the participants; and ethics in shadowing can be murky and researchers must make continuous ethical judgements while in the field.